Evaluation of the soil water content using cosmic-ray neutron probe in a heterogeneous monsoon climate-dominated region. (October 2017) - Nguyen, Hoang Hai; Kim, Hyunglok; Choi, Minha
Abstract: This study was conducted to evaluate the performance of a preliminary soil moisture product estimated from the cosmic-ray neutron probe (CRNP) installed at a densely vegetated and monsoon climate area, namely the Soil Moisture - FDR and Cosmic-ray (SM-FC) site in South Korea. In this study, different calibration approaches, considering soil wetness conditions, were evaluated to select the most appropriate calibration method for deriving the best cosmic-ray soil moisture at the SM-FC site. We tested the potential application of two horizontal-vertical weighting methods, including the linear and non-linear approaches, with regard to the specific characteristics of the SM-FC site. The comparison of the two weighting approaches for in-situ soil moisture measurement suggested that the linear approach provided better performance compared to the non-linear in term of representing field-average soil moisture within the CRNP footprint. Our calibration results revealed that dry condition-based calibration outperformed wet condition-based calibration. The comparison of the cosmic-ray soil moisture utilizing dry condition-based calibration showed reasonable agreement with the linear weighted average soil moisture estimated from the FDR sensor network, with RMSE = 0.035 m 3 m −3, and bias = −0.003 m 3 m −3 ; while the worst calibration solution with the wettest conditions had RMSE and bias values of 0.077 m 3 m −3 and 0.063 m 3 m −3, respectively. The application of a biomass correction significantly improved the cosmic-ray soil moisture product at the SM-FC site, resulting in the reduction of RMSE from 0.035 to 0.013 m 3 m −3 . A temporal stability analysis was conducted to demonstrate the feasibility of cosmic-ray soil moisture in representing soil moisture for a large heterogeneous SM-FC site. Our temporal stability analysis results indicated the representativeness of cosmic-ray soil moisture over an area with a high degree of heterogeneity, compared to single measurements from FDR stations.